2020
DOI: 10.1186/s12864-020-07194-6
|View full text |Cite
|
Sign up to set email alerts
|

The expression of the acarbose biosynthesis gene cluster in Actinoplanes sp. SE50/110 is dependent on the growth phase

Abstract: Background Actinoplanes sp. SE50/110 is the natural producer of the diabetes mellitus drug acarbose, which is highly produced during the growth phase and ceases during the stationary phase. In previous works, the growth-dependency of acarbose formation was assumed to be caused by a decreasing transcription of the acarbose biosynthesis genes during transition and stationary growth phase. Results In this study, transcriptomic data using RNA-seq and state-of-the-art proteomic data from seven time points of contr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 89 publications
(120 reference statements)
0
7
0
Order By: Relevance
“…With the fed-batch strategy, the engineered strain SIPI2207 made a breakthrough in acarbose yield and reached the highest titer ever reported (Table 1 ). Julian Droste found that the transcription level of acarbose synthesis genes showed a continuously decreasing trend from the early growth stage to the stationary stage, and acarbose was highly produced during the early growth stage and its production ceased during the stationary stage [ 45 ]. This finding also gave us some guidance by extending the growth phase can be an effective strategy for enhancing the production of acarbose.…”
Section: Discussionmentioning
confidence: 99%
“…With the fed-batch strategy, the engineered strain SIPI2207 made a breakthrough in acarbose yield and reached the highest titer ever reported (Table 1 ). Julian Droste found that the transcription level of acarbose synthesis genes showed a continuously decreasing trend from the early growth stage to the stationary stage, and acarbose was highly produced during the early growth stage and its production ceased during the stationary stage [ 45 ]. This finding also gave us some guidance by extending the growth phase can be an effective strategy for enhancing the production of acarbose.…”
Section: Discussionmentioning
confidence: 99%
“…Actinoplanes sp. SE50/110 alternative sigma factor gene ACSP50_0507 is strongly transcribed during the transition and early stationary growth phase, with a maximal transcript amount at the early stationary growth phase and therefore possibly influencing the cells during growth phase transition [ 12 ]. This σ B/F/G family protein (IPRO014322) of 270 amino acids features RNA-polymerase binding and −10 promoter recognition region 2 (IPRO07027), RNA-polymerase and extended-10 binding region 3 (IPRO07624) and −35 promoter element recognition region 4 (cd06171).…”
Section: Resultsmentioning
confidence: 99%
“…Within the acb gene cluster, regulatory elements are scarcely known. Determination of transcription start sites (TSSs) and operon structures [ 11 ] as well as transcription dynamics and protein abundancies [ 12 ] were major steps for the broader understanding of acb gene regulation. In prior works, the MalR type regulator AcrC was identified to bind within the acb gene cluster in the intergenic region between the genes acbE and acbD , but gene deletion did not result in an increased acarbose yield [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…AcbQ is one of the uncharacterized enzymes of Actinoplanes sp. SE50/110 and encoded within the acarbose biosynthesis gene cluster [22,30]. BLASTP analysis has shown similarities to MalQ proteins from other strains but also from its own Actinoplanes strain (ACSP50_7587, 42% identity, 56% similarity) [14].…”
Section: Simultaneous Assembly and Disassembly Of Linear α-14-glucansmentioning
confidence: 99%
“…Proteome analysis has shown that AcbQ features one of the highest protein stabilities during acarbose production compared to other Acb proteins. Its stability is post-translationally influenced, suggesting a high relevance in acarbose metabolism [22]. At a structural level, AcbQ has the highest similarity to MalQ from Haemophilus influenzae, which is a 4-α-glucanotransferase (EC 2.4.1.25) and belongs to the glycosyltransferase family [14,15].…”
Section: Introductionmentioning
confidence: 99%